THE DISREGARD OF THE CULTURAL DIMENSION IN TRANSLATION - Douah, Mohamed; Boudjelal, Mustapha (LLT Journal: A Journal on Language and Language Teaching, 2024)
The cultural turn in translation studies has propelled translation beyond a mere act of linguistic transposition. At this juncture, the cultural dimension has garnered significant attention, and translation has evolved into an act of cultural mediation. Within this framework, learners’ perceptions of the cultural dimension and classroom teaching practices are pivotal factors influencing translation quality. This study examines the classroom teaching practices vis-à-vis cultural learning and investigates learners’ perception of the significance of culture in translation. A survey questionnaire was administered to seventy-eight Master’s students of translation (Arabic-English-French) at the Institute of Translation, Oran University, Algeria. Additionally, an interview was conducted with 26 students from the same institute to accredit more validity and reliability to this study, to obtain more qualitative data, and to compare and crosscheck while interpreting the data from both the questionnaire and the interview. The analysis of the obtained data elucidated that cultural knowledge was impeached by classroom practices that do not foster intercultural learning despite learners’ positive attitudes towards the target cultures. This study offers some pedagogical recommendations to give the cultural dimension due attention in the translation classroom.